Analisis Faktor Pemicu Selisih Anggaran dengan Pendapatan Direktorat Jendral Hortikultura - Patrisya Putri Utami; Amira Dwi Aryani; Nur Aini Putri Daryanti; Siti Hindun; Azahra Elsa Mayori (Universitas 45 Surabaya, 2025)
This study aims to analyze the implementation of the budget and the factors triggering the budget variance in the Directorate General of Horticulture, Ministry of Agriculture of the Republic of Indonesia. Inaccuracies in budget planning and management can lead to deficits that affect operations and the success of programs. This research uses secondary data in the form of budget realization reports from 2020, with descriptive analysis methods to illustrate the variance between the budget and revenue. The results show that fluctuations in commodity prices, policy changes, and inaccuracies in budget planning are the main factors influencing the variance between the budget and realized revenue. Achieving revenue that exceeds the budget can indicate efficiency in resource management, but significant variances also suggest the need for improvements in budget planning in the future. Therefore, it is crucial for government agencies to conduct careful risk analysis and prepare realistic budgets to minimize undesired variances and enhance accountability in the management of public finances.